Voice-to-affect mapping: Inferences on language voice baseline settings - YANUSHEVSKAYA, IRENA; GOBL, CHRISTER; NI CHASAIDE, AILBHE (My University, 2017)
Modulations of the voice convey affect, and the precise mapping of voice-to-affect may vary for different languages. However, affect-related modulations occur relative to the baseline affect-neutral voice, which tends to differ from language to language. Little is known about the characteristic long-term voice settings for different languages, and how they influence the use of voice quality to signal affect. In this paper, data from a voice-to-affect perception test involving Russian, English, Spanish and Japanese subjects is re-examined to glean insights concerning likely baseline settings in these languages. The test used synthetic stimuli with different voice qualities (modelled on a male voice), with or without extreme f0 contours as might be associated with affect. Cross-language differences in affect ratings for modal and tense voice suggest that the baseline in Spanish and Japanese is inherently tenser than in Russian and English, and that as a corollary, tense voice serves as a more potent cue to high-activation affects in the latter languages. A relatively tenser baseline in Japanese and Spanish is further suggested by the fact that tense voice can be associated with intimate, a low activation state, just as readily as with the high-activation state interested.
INTERSPEECH 2017
Keywords: Affect; Voice source; Glottal; Perception; Cross-language; Voice quality; Prosody; Paralinguistic; Digital Humanities